2015
DOI: 10.1186/s13024-015-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel BACE inhibitor NB-360 shows a superior pharmacological profile and robust reduction of amyloid-β and neuroinflammation in APP transgenic mice

Abstract: BackgroundAlzheimer’s disease (AD) is the most common form of dementia, the number of affected individuals is rising, with significant impacts for healthcare systems. Current symptomatic treatments delay, but do not halt, disease progression. Genetic evidence points to aggregation and deposition of amyloid-β (Aβ) in the brain being causal for the neurodegeneration and dementia typical of AD. Approaches to target Aβ via inhibition of γ-secretase or passive antibody therapy have not yet resulted in substantial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 33 publications
2
133
0
3
Order By: Relevance
“…NB-360 inhibits the enzymatic activity of BACE, which is required for the generation of Aβ peptides from APP (12). Indeed, quantification of Aβ revealed a substantial reduction of the Aβ plaque burden ( (9,13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NB-360 inhibits the enzymatic activity of BACE, which is required for the generation of Aβ peptides from APP (12). Indeed, quantification of Aβ revealed a substantial reduction of the Aβ plaque burden ( (9,13).…”
Section: Resultsmentioning
confidence: 99%
“…The BACE inhibitor NB-360 was used in this study. A detailed description of the compound's in vitro and in vivo efficacy, pharmacokinetics, and brain penetration in various animal models has been described previously (9). Oral treatment with NB-360 was provided by incorporating the drug into food pellets (0.25 g/kg; Provimi Kliba, Kaiseraugst, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were attributed to the ability of NB‐360 to reduce the formation of Aβ oligomers. When researchers reintroduced soluble Aβ oligomers to these mice, the positive implication of NB‐360 was reverted and the mice showed again the typical symptoms of AD . Therefore, these in vivo studies revealed evidence on the implication of BACE1 inhibitors as a valid approach to tackle AD and that Aβ oligomers are having a downstream effect on AD progression …”
Section: Alzheimer's Disease Pathology and Targetsmentioning
confidence: 97%
“…Moreover, many in vivo studies confirmed that β‐secretase play a vital role in AD progression and the use of BACE1 inhibitors improved the neurological function and surpassed the neurological defects imposed in mice of AD model . For example, in a recent study utilizing NB‐360 as BACE1 inhibitor in mice with familial Alzheimer disease, the administration of this agent resulted in the enhancement of neuronal activity and the improvement of memory . These effects were attributed to the ability of NB‐360 to reduce the formation of Aβ oligomers.…”
Section: Alzheimer's Disease Pathology and Targetsmentioning
confidence: 98%